Zachowania ryzykowne młodzieży = Risky behaviors of teenagers - Baranowska, Aneta (Journal of Education, Health and Sport, 2016)
Baranowska Aneta Sylwia. Zachowania ryzykowne młodzieży = Risky behaviors of teenagers. Journal of Education, Health and Sport. 2016;6(6):517-530. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.56418 http://ojs.ukw.edu.pl/index.php/johs/article/view/3639 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.05.2016. Revised 25.06.2016. Accepted: 27.06.2016. ZACHOWANIA RYZYKOWNE MŁODZIEŻY RISKY BEHAVIORS OF TEENAGERS Aneta Sylwia Baranowska1 1 Uniwersytet im. Adama Mickiewicza w Poznaniu; Wydział Studiów Edukacyjnych; e-mail: anet.bar@gmail.com Streszczenie W artykule została podjęta problematyka zachowań ryzykownych przejawianych przez współczesną młodzież. Autorka tekstu dokonała zwięzłej charakterystyki najczęściej występujących wśród młodych ludzi zachowań problemowych, takich jak: palenie papierosów, nadużywanie alkoholu, narkotyków i dopalaczy; ryzykowna aktywność seksualna; okaleczanie własnego ciała (autoagresja); nadmierne opalanie się. Następnie, odwołując się do teorii czynników ryzyka i czynników chroniących, koncepcji resilience, modelu ekologicznego Bronfenbrennera oraz Teorii Zachowań Problemowych, zwróciła uwagę na czynniki, które intensyfikują prawdopodobieństwo występowania zachowań ryzykownych u adolescentów oraz na czynniki, które wzmacniają ogólny potencjał zdrowotny człowieka i tym samym jego odporność na działanie tych pierwszych. Opracowanie kończy ilustracja zadań, jakie stoją przed osobami prowadzącymi działania profilaktyczne, w związku z rozpowszechnianiem się wśród nastolatków zachowań problemowych. Słowa klucze: zachowanie ryzykowne, adolescenci, czynniki ryzyka, czynniki chroniące, profilaktyka. Summary The article touches upon risky behaviors manifested by contemporary teenagers. The article characterizes the most frequent types of risky behaviors among young people, such as: smoking cigarettes, alcohol, drugs and designer drugs abuse, risky sexual contacts, self-mutilation (self-injury) and excessive sunbathing. The author also appeals to the theory of risk and protective factors, notion of resilience, ecologic model of Bronfenbrenner, and the theory of problem behavior in order to point out to the factors which intensify the probability of risky behaviors of adolescents as well as the factors which enhance the overall health potential of a person and thus his resistance to such factors. The research ends with a list of tasks that people responsible for preventive actions are facing due to the proliferation of troublesome behavior among teenagers. Key words: risky behaviors, teenagers, risk factors, protective factors, prevention.